Evidence of plasmotomy in Blastocystis hominis - Tan, T.C.; Suresh, K.G. (2007)
Blastocystis hominis has been regarded as an enigmatic parasite as many aspects of its basic biology remain uncertain. Many reproductive processes have been suggested for the organism; however, to date, only the binary fission has been proven. Plasmotomy is one of the modes of reproduction previously suggested to be seen in in vitro cultures. The present study provides trichrome and acridine orange staining evidence for the existence of nucleic acid suggestive of division of nucleus into multinucleate forms with the respective cytoplasm dividing giving rise to two or three progeny B. hominis. Transmission electron micrographs further confirmed that these daughter cells had respective surrounding surface coat, mitochondria, and vacuoles.